Relationship of serum gastrin response to lower oesophageal sphincter pressure. Issue 2 (February 1976) - Dent, J; Hansky, J
Abstract : The role of gastrin in controlling lower oesophageal sphincter pressure (LESP) has been examined by measurement of LESP and serum gastrin response to a test protein solution and a control solution in humans. Both solutions were associated with significant (P less than 0-005) rise in LESP, but serum gastrin rose significantly (P=0-05) only after the protein solution. The rise in serum gastrin after the protein solution preceded the rise in LESP by 30 minutes. These results suggest that the lower oesophageal sphincter response to feeding may be independent of protein and is unrelated to gastrin release.